Diffusive transport of adsorbed n-alkanes along e-beam irradiated plane surfaces and nanopillars - Zhdanov, Gleb S.; Lozhkin, Maksim S. (Diffusion Fundamentals, 2017)
Diffusion of adsorbed n-alkanes was studied by means of electron beam induced deposition (EBID) technique. Carbon ring-like and pillar-like deposits were produced on bulk and thin substrates in a scanning electron microscope (SEM) operated in a “spot” mode. Residual nalkanes used as a precursor gas were delivered to the beam interaction region (BIR) via surface diffusion. The model of adsorbate diffusion along a heterogeneous surface with different diffusion coefficients D1 and D2 outside and inside the BIR, respectively, was proposed to explain the measured deposition rates. The estimates for diffusion coefficients ranging from 1x10-10 to 1x10-7 cm2s-1 at room temperature on surfaces with different roughness were obtained. These estimates most likely should be attributed to n-decane molecules expected to play the key role in the deposition process. Clusters of polymerized molecules produced by irradiation were assumed to act as effective traps hampering surface diffusion. For high D1/D2 ratios the deposition rates were found to be practically independent of the substrate material and initial roughness.